Evaluation of General Synthesis Procedures for Bioflavonoid–Metal Complexes in Air-Saturated Alkaline Solutions - Yao, Yuanyong; Zhang, Meng; He, Laibing; Wang, Yunyang; Chen, Shixue (Frontiers in Chemistry, 2020)
The general synthesis methods of bioflavonoid–metal complexes are considered to be unreliable due to the instability of flavonoids in air-saturated alkaline solutions. In this study, dihydromyricetin (DHM), as a representative bioflavonoid, was selected for complexation with various transition metal ions in an air-saturated alkaline solution to form DHM–metal(II) complexes, following the general synthetic procedure. After characterization, the metal complexes were hydrolyzed to observe the stability of DHM under acidic conditions via HPLC. The effects of synthetic conditions (metal ion, alkalinity, and reflux time) on DHM stability were then investigated by UV-vis spectroscopy and HPLC. Finally, using electron paramagnetic resonance, DHM and its analogs were observed with DMPO (5,5-dimethyl-1-pyrroline-N-oxide) to form a relatively stable free radical adduct. Multiple peaks corresponding to unknown compounds appeared in the LC spectra of the DHM–metal(II) complexes after hydrolysis, indicating that some DHM reacted during synthesis. Subsequently, the transition metal ion and solution alkalinity were found to have notable effects on the stability of free DHM. Furthermore, DHM and several of its analogs generated the superoxide-anion radical in air-saturated alkaline solutions. Their capacities for generating the superoxide anion seemed to correspond to the number and/or location of hydroxyl groups or their configurations. Interestingly, DHM can react with the superoxide anion to transform into myricetin, which involves the abstraction of a C3–H atom from DHM by O2−. Therefore, the general synthetic procedure for bioflavonoid–metal complexes in air-saturated alkaline solutions should be improved.